2004
DOI: 10.1021/jo049672o
|View full text |Cite
|
Sign up to set email alerts
|

Enantiodivergent Synthesis of Pyrrolo[2,1-a]isoquinolines Based on Diastereoselective Parham Cyclization and α-Amidoalkylation Reactions

Abstract: Enantiodivergent synthesis of C-10b-substituted pyrrolo[2,1-a]isoquinolines starting from an enantiomerically pure N-phenethylnorborn-5-en-endo-2,3-dicarboxyimide 3a, with a 2-exo-hydroxy-10-bornylsulfinyl group as a chiral auxiliary, has been developed. The key transformations are derived from diastereoselective intramolecular cyclization of aryllithiums and alpha-amidoalkylation reactions, with the ethylidene bridge of the norbornene moiety dictating the stereochemical outcome in both types of reactions. Thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Lete et al have reported the asymmetric synthesis of pyrrolo[2,1-a]isoquinolines 54 starting from enantiopure sulfinylmaleimide 49 (Scheme 12). 32 Reaction of 49 with cyclopentadiene followed by alkyl lithium, afforded ahydroxylactams 50 in quantitative yields as single diastereoisomers. Treatment of 50 with an excess of TFA at room temperature furnished isoquinolines 51, together with their derivatives 52, in which trifluoroacetylation of the hydroxyl group of the auxiliary had occurred.…”
Section: C-s Cleavagementioning
confidence: 99%
“…Lete et al have reported the asymmetric synthesis of pyrrolo[2,1-a]isoquinolines 54 starting from enantiopure sulfinylmaleimide 49 (Scheme 12). 32 Reaction of 49 with cyclopentadiene followed by alkyl lithium, afforded ahydroxylactams 50 in quantitative yields as single diastereoisomers. Treatment of 50 with an excess of TFA at room temperature furnished isoquinolines 51, together with their derivatives 52, in which trifluoroacetylation of the hydroxyl group of the auxiliary had occurred.…”
Section: C-s Cleavagementioning
confidence: 99%
“…Terpene thiols can be used as intermediates in organic synthesis to produce sulfochlorides, [15–17] sulfonamides, [18] sulfides, [4,8,9,19] disulfides, [5,20] sulfenimines and sulfinimines [7,21–25] . Chiral monoterpene hydroxythiols can also be used as chiral ligands or organocatalysts in asymmetric catalysis and as chiral auxiliaries in asymmetric synthesis [26–36] . Previously, we have developed methods for producing monoterpene menthane, [20,21] bornane, [22] pinane [37] and carane thiols [38] …”
Section: Introductionmentioning
confidence: 99%
“…For synthetic chemists, the RDA reaction has become a valuable tool for their research towards the design and synthesis of novel heterocyclic scaffolds, because of its efficiency in introducing a double bond into a heterocyclic skeleton [40] along with enantiocontrolled [41] and enantiodivergent [42] syntheses of heterocyclic compounds.…”
Section: Introductionmentioning
confidence: 99%